Ensuring quality pharmacokinetic analyses in antimicrobial drug development programs. (October 2017) - Lakota, Elizabeth A; Bader, Justin C; Rubino, Christopher M
Highlights: Robust pharmacokinetic analyses should be used to optimize all stages of development. Various methodologies are available to analyze pharmacokinetic data. Study design from a pharmacokinetic perspective is critical. Accurately and precisely collected pharmacokinetic data are essential. Abstract : Pharmacokinetic studies and analyses can be expensive, time consuming, and labor intensive. However, it is crucial to understand that much of what happens in antimicrobial drug development, such as dose-selection and clinical study design, can be optimized with a strong understanding of the underlying pharmacokinetics of an agent. In this way, pharmacokinetics forms the bedrock of a pharmacometric approach to antimicrobial development. Thus, pharmacokinetic analyses must be considered an integral part of a drug's development strategy and studies must be planned and designed accordingly. This paper provides a brief overview of pharmacokinetic analysis methods, including best practices and their use in the context of a drug development program. In addition we will conclude with an overview of proper design and conduct of pharmacokinetic studies to optimize their use in evaluating clinical study data.